Oligoclonal bands as predictors of multiple sclerosis in clinically isolated syndrome - Klaudia Sapko; Anna Szczepańska-Szerej; Marcin Kulczyński; Michał Marciniec; Konrad Rejdak (Kazimierz Wielki University, 2018)
Clinically Isolated Syndrome (CIS) is the first episode of inflammatory and demyelinating symptoms. According to the classification criteria of multiple sclerosis (MS) from 2013, CIS is defined as the first clinical manifestation of the disease. McDonald's 2010 criteria, considered the gold standard in the diagnosis of MS, are based on the clinical symptoms and the characteristic changes in magnetic resonance imaging (MRI). Unfortunately, up to 60-70% of patients with CIS do not meet the criteria for diagnosing MS at an early stage. At the same time, approximately 85% of patients with CIS will develop clinically defined MS (CDMS) in the future. When looking for other diagnostic tools, attention was paid to the role of oligoclonal bands (OBs) as predictors of MS development. Oligoclonal bands are immunoglobulins produced intrathecally by B-lymphocytes and plasma cells. Their level is examined in cerebrospinal fluid (CSF) collected by lumbar puncture. Studies carried out on a group of patients with CIS showed that people with positive test results for oligoclonal bands are twice as likely to develop MS than people with negative OBs. These conclusions are reflected in the revised McDonald's criteria in 2017, where OBs are used in the diagnosis of CIS patients with absence of new symptoms of the disease and changes in MRI. Early diagnosis makes possible to implement modifying disease drugs in the initial stage and, consequently, to achieve better therapeutic effects. The emphasis is also put on the development of other predictors in body fluids, which are effective in the diagnosis of people with CIS and negative oligoclonal bands. Many factors, including Epstein-Barr virus, chitinase-3 like 1, chitinase-3 like 2, chitotriosidase, multi-specific response to measles, rubella and varicella known as "MRZ reaction" or T-cell gene mutation are studied as a potential risk factors for MS development. Their use in diagnostics would improve the detection of MS in earlier stages, and thus the treatment of larger population of patients.